Validity, reliability, and readability of single-item and short physical activity questionnaires for use in surveillance: A systematic review - Tcymbal, Antonina; Messing, Sven; Mait, Rachel; Galindo Perez, Roberto; Akter, Taiyeba; Rakovac, Ivo; Gelius, Peter; Abu-Omar, Karim (PLoS ONE, 2024)
Background Accurate and fast measurement of physical activity is important for surveillance. Even though many physical activity questionnaires (PAQ) are currently used in research, it is unclear which of them is the most reliable, valid, and easy to use. This systematic review aimed to identify existing brief PAQs, describe and compare their measurement properties, and assess their level of readability. Methods We performed a systematic review based on the PRISMA statement. Literature searches were conducted in six scientific databases. Articles were included if they evaluated validity and/or reliability of brief (i.e., with a maximum of three questions) physical activity or exercise questionnaires intended for healthy adults. Due to the heterogeneity of studies, data were summarized narratively. The level of readability was calculated according to the Flesch-Kincaid formula. Results In total, 35 articles published in English or Spanish were included, evaluating 32 distinct brief PAQs. The studies indicated moderate to good levels of reliability for the PAQs. However, the majority of results showed weak validity when validated against device-based measurements and demonstrated weak to moderate validity when validated against other PAQs. Most of the assessed PAQs met the criterion of being "short," allowing respondents to complete them in less than one minute either by themselves or with an interviewer. However, only 17 questionnaires had a readability level that indicates that the PAQ is easy to understand for the majority of the population. Conclusions This review identified a variety of brief PAQs, but most of them were evaluated in only a single study. Validity and reliability of short and long questionnaires are found to be at a comparable level, short PAQs can be recommended for use in surveillance systems. However, the methods used to assess measurement properties varied widely across studies, limiting the comparability between different PAQs and making it challenging to identify a single tool as the most suitable. None of the evaluated brief PAQs allowed for the measurement of whether a person fulfills current WHO physical activity guidelines. Future development or adaptation of PAQs should prioritize readability as an important factor to enhance their usabilit